The window as a symbol of the architect's gaze - de Molina, Santiago (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
The history of the architectural gaze follows a linear course, except for the one that occurs in the Renaissance. At that moment, with the appearance of perspective and the consolidation of the window trope, architecture became aware of the true role of the gaze. From a historical point of view, the vision of perspective has been privileged over the window way of seeing the world. But the symbolic, physical, and social richness of the window is meaningful. The text unravels the history of the window from a phenomenological and psychic approach. If the painting has appropriated the window to emphasize its delimiting power, architecture claims it as an intertextual space from which to think itself. The window symbolizes the image of the architectural gaze insofar as it frames, focuses and discards part of the world. From ancient times, to Ledoux and Le Corbusier, the window allows us to see through it, at the same time as it allows us to see the gaze itself. The window condenses the architectural gaze thanks to the material and psychological image it represents. In short, it shows, by itself, the powerful phenomenology of the architect's gaze.
Keywords: Gaze; Window; View; Perspective; Architecture